The Effect of Corncob (Zea mays) Extract Cream on the Number of Melanin Pigments of Guinea Pig Exposed to Ultraviolet - Pasid Harlisa; Sita Mahardika; Suryani Yuliyanti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Exposure to Ultraviolet B (UVB) rays on the skin causesmany problems, including pigmentation and aging effect. Hence, protection against it is needed. Purpose: The study aimedto determine the effect of corncob extract cream on the number of melanin pigments in guinea pig skins exposed to UVB rays. Methods: Anexperimental post-test-only control group study was conducted on the 25 guinea pigs. The guinea pigs were divided randomly into five groups: group I without cream, group II cream base, group III hydroquinone cream, group IV 30% corncob extract cream, and group V 40% corncob extract cream. The cream was given daily for 20 minutes before UVB exposure and 4 hours after UVB exposure. The total dose of UVB exposure was 780 mJ / cm2 for 28 days. The amount of melanin pigment was calculated using the CX21 image J. Result: The number of melanin pigment in groups I, II, III, IV, and V were 22.8±0.4 cells, 18±0.3 cells, 6.3±3.1 cells, 13.8±0.2 cells, and 9.4±0.5 cells, respectively. Asignificantlydifferent value of One way ANOVA test was <0.05. Thus, there was a difference in the number of melanin pigments between the five groups. LSD post-hoc test showed differences in each group (p <0.05). Conclusion: 40% corn cobs extract cream effectively decreased the number of melanin pigment in guinea pigs exposed to UVB rays.